629.IMPACT OF REK BITOLA UPON PHYSICAL AND CHEMICAL PROPERTIES OF THE SOIL - Slobodan, Bogoevski; Bosko, Boskovski; Gordana, Ruseska (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
Contamination of soil by air sediment emitted from coal based thermal power plants is one of the basic ecological issue. The aim of this research is to define the impact of production of REK Bitola on the soils from defined microlocality in Pelagonia basin. Chemical, mineralogical and granulometric analyses were performed upon the soil samples. Also basic physical properties of the soil are determined. The chemical composition of the air sediment was also determined. According to the measured values and statistical data of REK Bitola, an average cumulative deposited quantity of air sediment is calculated, as well as the cumulative deposited quantity of trace elements in soil. The deposited air sediment has a negative impact on some of the basic physical and chemical properties of soil, but has no significant effect on the change in porosity and soil properties resulting from it.